Koinocystididae and Gnathorhynchidae (Platyhelminthes: Rhabdocoela: Kalyptorhynchia) from the Galapagos, with the description of three new species - Reygel, Patrick C.; Willems, Wim R.; Artois, Tom J. (Zootaxa, 2011)
Seven species of eukalyptorhynch flatworms from the Galapagos Islands are reported. Six of them belong to the taxon Koinocystididae Meixner, 1924, three of which are new to science. Two of these new species can be attributed to the genus Itaipusa Marcus, 1949 based on the construction of the prostate vesicle and the general structure of the female system. Itaipusa biglandula n. sp. is characterised by a very short, muscular, unarmed penis papilla, whereas I. renei n. sp. is characterised by the presence of a cirrus armed with minute scales, and two large, blunt hooks in the male atrium. The third new species cannot be placed in any existing taxon and therefore a new genus is erected: Galapagetula annikae n. gen. n. sp.. It is characterised by a straight and rather long cirrus, armed with small spines, and a clearly bipartite bursa in the female system. Additional morphological information is given for the three known species of Koinocystididae: I. divae Marcus, 1949; I. variodentata (Karling, Mack-Fira & Dörjes, 1972) Karling, 1978 and Utelga heinckei (Attems, 1897) Karling, 1954. For I. divae a new locality from Curaçao is also mentioned. The seventh species is a species of Gnathorhynchidae: Prognathorhynchus eurytuba Ax & Armonies, 1987, for which new morphological information on the organisation of the genital system is given.